Keputusan Pembelian Ditinjau Dari Citra Merek Dan Gaya Hidup Konsumen Rm Sambel Alu Bandar Lampung - Dinata, Yazid Hajrian; Wakhid, Ali Abdul; Purnama, Rahmad (Universitas Islam Negeri Raden Intan Lampung, 2022)
Purchasing decisions in urban communities are not only based on product taste or quality, but also other factors such as brand image and lifestyle which most local culinary entrepreneurs pay little attention to. This shows that urban people with high mobility want a product that is able to answer their problems, namely food products that are fast, practical and prestige. This study aims to reveal and analyze consumer purchasing decisions in a review of brand image and lifestyle, is there a positive and significant relationship between brand image and lifestyle and purchase decisions at RM Sambel Alu Bandar Lampung consumers.This research is a quantitative study that uses a psychological measurement tool with a Likert scale model as a method of collecting research data. Purchase decision scale with Cronbach alpha (α = 0.815), brand image scale with Cronbach alpha (α = 0.813), and lifestyle scale with Cronbach alpha (α = 0.936). The population in this study were consumers of RM Sambel Alu with certain criteria determined by the researcher. To ensure that the sample truly represents the entire population, the researcher chose purposive sampling and accidental sampling techniques as a reference in sampling. Analysis of the research data was carried out using a two-predictor regression analysis technique which in the calculation process was assisted by the SPSS 21 computer program. The results of the study show that there is a positive and significant relationship between brand image and lifestyle and consumer purchasing decisions of RM Sambel Alu. The results of the regression analysis show that the two independent variables make an effective contribution (SE) of 36.2% to purchasing decisions (R2=0.362; R=0.601; F=27.459; sig. 0.000 (p<0.01). Meanwhile, the remaining 63.8% can be influenced by variables other than this research.X1-Y=0.360; sig.0.000 (p<0.01) means that there is a significant positive relationship between brand image and purchasing decisions.X2-Y= 0.581; sig.0.000 (p<0.05) means there is a positive relationship significant relationship between lifestyle and purchasing decisions. Keywords: Purchase Decision, Brand Image, Lifestyle, Consumers, Local Culinary.